2022
DOI: 10.3389/fpubh.2022.893439
|View full text |Cite
|
Sign up to set email alerts
|

Measuring patients' satisfaction toward health tourism in Malaysia through hospital environment, nutritional advice, and perceived value: A study on Chinese exchange students

Abstract: Malaysia is a reputed destination for health tourism in the Asia Pacific region for its hospitable nature and good quality of service. Patients' satisfaction has been a key concern in health tourism to maintain the flow of tourists' arrival for medical purposes. By considering the importance of health tourism and patients' satisfaction in Malaysia, this study aimed to examine the influence of hospital environment, nutritional advice, perceived value on patients' satisfaction. This study is cross-sectional in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…This study makes several methodological and theoretical contributions. First, in terms of methodology, previous studies on patient satisfaction have used cross-sectional questionnaires and descriptive studies (69,70), which may be geographically limited and make it difficult to establish a causal relationship between determinants and satisfaction. Second, many studies related to recommendation sources [e.g., (19,20)] have shown that online consumer reviews are the main source of information for consumers' decisions.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…This study makes several methodological and theoretical contributions. First, in terms of methodology, previous studies on patient satisfaction have used cross-sectional questionnaires and descriptive studies (69,70), which may be geographically limited and make it difficult to establish a causal relationship between determinants and satisfaction. Second, many studies related to recommendation sources [e.g., (19,20)] have shown that online consumer reviews are the main source of information for consumers' decisions.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Tourists with the push motivation may perceive the high value of health and wellness tourism [13,42]. For instance, individuals desire to escape their routines when perceiving the health and emotional value of health and wellness tourism [66]. When it is felt that health and wellness tourism cost including time and money is acceptable, travelers may be able to generate a sense of worthiness towards the tourism [46,47].…”
Section: Perceived Value As a Mediatormentioning
confidence: 99%
“…Individuals may be attracted by health and wellness products or services and a healthy environmental atmosphere, and for the sake of their health status improvement, they likely perceive a high value of health and wellness tourism [42,54,66]. Interpersonal motivation is an antecedent to holistic tourism and may also play a role in the choice of health and wellness tourism, especially when there are older adults or chronic disease patients in the tour groups [42,66,67]. Based on this, we propose the hypothesis as follows.…”
Section: Perceived Value As a Mediatormentioning
confidence: 99%
“…Patient satisfaction is something that must be maintained by a hospital or health clinic so that the image of the service can remain of high quality and its existence can continue to survive in society (Lee & Lee, 2022;Li et al, 2022). Patient satisfaction is a global indicator of a health service accreditation standard (Organization, 2022), without patient satisfaction, it cannot be ascertained whether a health service is of good standing (Matovu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Satisfaction is the customer's response to the discrepancy between the previous level of importance and the actual performance he feels after use. Patient satisfaction is an important indicator that must be considered in health services (Lotfi et al, 2019). One of the factors that determine satisfaction is the patient's perception of service quality which focuses on seven dimensions, namely tangible, reliability, responsiveness, empathy, responsibility and cost (Kapikiran et al, 2022).…”
Section: Introductionmentioning
confidence: 99%